Ethical Issues Faced by Psychologists in Medical Settings and Ways to Deal with Them - Anindita Mukherjee, R. Kanakalakshmi, Golda Sahaya Rani. R, S. Karthika, M. R. Suchitra (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Psychologists are faced with many ethical challenges that are very different from any other profession in the medical field. Ethics is one of the most important things in any profession to maintain quality and deliver the best results. The purpose of this article is to investigate the ethical issues that are faced by psychologists in the medical field along with the steps that they can take to deal with these ethical issues. The research has used secondary sources to gather the required information and provide a concise idea of the entire subject matter. There are various ethical issues such as informed consent, confidentiality, conflict of interest, misconceptions, and vulnerability among others. This research has discussed various methods to deal with the ethical challenges that are commonly faced by psychologists. There is still a need for further discussion on the subject and the challenges are something that needs to be researched in the future.